Long‐term dynamics of rockslides and damage propagation inferred from mechanical modeling. Issue 4 (31st October 2013) - Lacroix, P.; Amitrano, D.
<x xml:space="preserve">Abstract</x> [1] Long‐term observations of large active rockslides show accelerating deformation over many thousands of years since the last deglaciation. The effect of deglaciation on slope stability is however poorly understood due to (1) limited long‐term observations and (2) a complex interaction between glacier retreat and hydrogeological, mechanical, and morphological processes. To assess the sensitivity of rockslide dynamics to these different processes, a model of progressive damage through intact rock mass is developed in this study, based on the finite element method. This model uses time‐to‐failure laws based on rock laboratory creep experiments. It is able to reproduce progressive damage localization along shear bands associated with strain rate acceleration as observed during tertiary creep. The model reproduces the different phases of deformation associated with morphologies typical of large rockslides. This model is thus suitable for simulating the dynamics of large rockslides and the transition from initiation to rapid sliding. The sensitivity of rockslide kinematics and morphology to different mechanical properties is analyzed. This analysis shows that the time evolution of the rockslide can be inferred with the knowledge of only one time parameter, independent of the knowledge of the mechanical properties of the rock mass. This parameter is here chosen as the time when the summit slope displacement has reached 10 m, a parameter that can be estimated with cosmogenic dating. The model is then used to study the effects of deglaciation on the valley flank stability and the formation of large rockslides. This study shows that the deglaciation velocity can affect the morphology of the rockslide, with the shear band of the rockslide emerging at higher elevation as the velocity decreases. We also show that the response to the deglaciation can last several thousands of years after the glacier retreat.